If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5X + 7 = 4 Reorder the terms: 7 + 0.5X = 4 Solving 7 + 0.5X = 4 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 0.5X = 4 + -7 Combine like terms: 7 + -7 = 0 0 + 0.5X = 4 + -7 0.5X = 4 + -7 Combine like terms: 4 + -7 = -3 0.5X = -3 Divide each side by '0.5'. X = -6 Simplifying X = -6
| 6x+13y=(-2) | | 7x-4=3x-5 | | 1-4x+2=15 | | 4(X+5)=24 | | 3n-2+6=-14 | | 9y-5y=8 | | 3m-3+4m=4 | | 6x-3-2x-10=12 | | -5m+2m=6+m+30 | | 5t-2-t=14 | | 2s-3s=20 | | 2s-3s=220 | | -3(a-2)+1=28 | | 4x-3=5x-7 | | 14n+2=-50 | | -2x-18=6 | | -7m-4=12 | | 7x+6-2x=-9+2x | | 9x-4=-14 | | 10x=58 | | -3x+6=-9 | | 10x=6x+345 | | 7.5a+1.51=-32.99 | | 44=-4(z+3) | | 9x=4x+55 | | 2(x+8)=10x-4 | | 5x+8=-3x+40 | | 6a-6=2a+14 | | 5=5 | | 11x+15=180 | | 4y+14y+40=580 | | 2(x+4)=x+10 |